Oil Thermal Annealed Nano-structured Indium Tin Oxide Thin Films for Display Applications - Q.Z., Mehdi; Al-Dabbagh, Jinan B.; Mahmoud Ahmed, Naser; V G, Chigrinov; Hegde, Gurumurthy (wiley online library, 2014)
Indium tin oxide-coated thin films (200 nm) are deposited on glass substrates by using R.f. sputtering technique. Here, we investigate the influence of new technique of treatment, which is called asâoil thermal annealingâon the nano-structured indium tin oxide thinfilms atfixed temperature (150 Â°C) which improves adhesion strength, electrical conductivity and optical properties (transmittance) of the films. Oil thermal annealing is used to reduce inherent defects that may be introduced during the prepared thinfilm and cooling processes. Proposed technique is highly suitable for liquid crystal displays,solar cells and organic light emitting diodes, and many other display-related applications.